PERANAN RETRIBUSI OBYEK PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GRESIK (STUDI KASUS PADA WISATA RELIGI MAKAM SUNAN GIRI DI KABUPATEN GRESIK) - INDAH KURNIA SARI, NUR Kurnia (Jurnal Akuntansi AKUNESA, 2014)
According to the Law of the Republic of Indonesia Number 28 Year 2009 about Regional Taxes and Regional Retribution is one of local revenue sources.One of them is Gresik District takes retribution of tourism places and sport.The formulation of this problem is how many contribution retribution of religious tourism Sunan Giri on Own Local Revenue start from 2009-2013 and what are the factors that cause contribution changes every year.This research of methods by using qualitative descriptive method.The results showed that there is an increase of fare start from Rp500 on 2009-2010 become Rp1000 on 2011,it will also increase retribution revenue of religious tourism Sunan Giri that gives contribution for about 22,15% on Own Local Revenue.However,in 2012 contribution revenue was decrease become 18,71% due to the growing proportion of Own Local Revenue increase than last year.While in 2013 increased to 20,89% because there is an increase total visitors.Keywords: Own Local Revenue, retribution tourism places and sport, contribution.